IMPLEMENTASI SMART ENVIRONMENT DI KOTA DENPASAR DALAM MEWUJUDKAN DENPASAR SMART CITY (Studi Kasus: Dinas Lingkungan Hidup dan Kebersihan Kota Denpasar) - Kusumasanti, I Gst Ayu Nyoman; Wismayanti, Kadek Wiwin Dwi; Supriliyani, Ni Wayan (CITIZEN CHARTER; Vol 3 No 2 (2023): Administrasi Publik 2023, 2024)
Smart Environment is one of the six dimensions in the Smart City Master Plan for Denpasar City which explains smart environmental management strategies in Denpasar City, one of which is waste management. This policy aims to create sustainable waste management and reduce the amount of waste taken to the TPA. The purpose of this study is to find out how the smart environment is implemented in Denpasar City, especially in waste management. Through the theory of policy implementation according to Van Meter and Van Horn. The results of this study are that the implementation of smart environment in Denpasar City, especially in waste management, has achieved good results on several indicators such as inter-organizational communication, economic, social and political conditions and attitudes of implementers. However, it is still not maximal in terms of standard indicators and objectives, resources, and characteristics of implementing organizations.